2010
DOI: 10.1111/j.1365-3059.2010.02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic features of Pseudomonas syringae pv. actinidiae isolated during recent epidemics of bacterial canker on yellow kiwifruit (Actinidia chinensis) in central Italy

Abstract: Pseudomonas syringae pv. actinidiae (Psa) was identified as the causal agent of severe epidemics of bacterial canker on Actinidia chinensis (yellow kiwifruit) in central Italy occurring during 2008-9. A total of 101 strains were obtained from infected leaves, twigs, branches and trunks of cvs Hort16A, Jin Tao and CK3. Outbreaks were also found on A. deliciosa cv. Hayward. A representative set of 21 strains were compared with other Psa strains isolated from previous outbreaks in Japan and Italy as well as with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
150
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 17 publications
7
150
1
1
Order By: Relevance
“…While in vitro studies show clear antibiotic activity, there is limited evidence for the antibiotic action of chitosan against major bacterial pathogens in planta. Chitosan toxicity has been shown in the major bacterial plant pathogen Pseudomonas syringae [39], but again, this study was conducted in vitro. Chitin in the form of ground shrimp waste was found to control the pathogen Streptomyces scabies, which causes scab disease on potato tubers [40], minimising the infection of the scab susceptible potato cultivar "Bentje" to 4%, compared to 22% in the control group.…”
Section: Effectiveness Of Chitin-based Treatments Against Bacterial Pmentioning
confidence: 99%
“…While in vitro studies show clear antibiotic activity, there is limited evidence for the antibiotic action of chitosan against major bacterial pathogens in planta. Chitosan toxicity has been shown in the major bacterial plant pathogen Pseudomonas syringae [39], but again, this study was conducted in vitro. Chitin in the form of ground shrimp waste was found to control the pathogen Streptomyces scabies, which causes scab disease on potato tubers [40], minimising the infection of the scab susceptible potato cultivar "Bentje" to 4%, compared to 22% in the control group.…”
Section: Effectiveness Of Chitin-based Treatments Against Bacterial Pmentioning
confidence: 99%
“…The epidemic affecting 'Hort16A' in Italy was caused by a strain that appeared to be more virulent than a strain reported in 1994 (Scortichini 1994;Balestra et al 2009;Ferrante and Scortichini 2010). The epidemic in Italy has caused severe vine losses, with removal of entire orchards as a consequence (Balestra et al 2009).…”
mentioning
confidence: 99%
“…BLAST analysis of these amplicons showed that the regions were 100% homologous to the respective Psa sequences in GenBank, accessions FN652889 and FN652897 from the 2008 epidemic in Italy (Ferrante and Scortichini 2010) for the gyrB gene, and FN433222 and AB016304 from the type strain (Kw-11, ICMP 9617) for the rpoD gene. Analysis of neighbour joining trees generated in Geneious Pro (ver.…”
mentioning
confidence: 99%
“…A recent outbreak of bacterial canker is devastating the Italian kiwifruit industry. The strains isolated from recent outbreaks in Italy are different from those isolated before 2008, or from those isolated from Japan and Korea (Ferrante and Scortichini, 2010;Vanneste et al, 2010).…”
mentioning
confidence: 99%
“…In previous works, two different BOX-PCR patterns depending on isolation year were described for P. syringae pv. actinidiae strains (Ferrante and Scortichini, 2010;Vanneste et al, 2011a). It was shown that P. syringae pv.…”
mentioning
confidence: 99%